The 1st International Electronic Conference on Agronomy 2021
DOI: 10.3390/iecag2021-09711
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxic Effect of Essential Oil from Hyssop (Hyssopus officinalis L.) against Spring Wheat and White Mustard

Abstract: Hyssop essential oil is a rich source of biologically active compounds. This study aimed to characterize the chemical composition of essential oil from the hyssop herb and its phytotoxicity against germination and initial growth of wheat and mustard. The main compounds of the oil were identified as isopinocamphone and pinocamphone. In a Petri dish experiment, the oil mainly inhibited the germination and initial growth of wheat, whereas mustard was less affected. In conclusion, hyssop oil displays phytotoxic po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…The main constituent was isopinocamphone that accounted for 34.00%, followed by pinocamphone (21.27%), β-Pinene (13.19 %), β-Phellandrene (13.10), α-Thujene (3.89 %) and Bicyclo-germacrene (3.47%). These results are well-matched with those of Jop et al, (2021), Aćimović et al, (2021, Hristova et al, (2015), Said-Al Ahl et al, (2015) and Stappen et al, (2015). They showed that isopinocamphone was the main component and followed by pinocamphone, β-pinene (8.8%), D-germacrene, bicyclo-germacrene, (E)-βcaryophyllene and α-elemol.…”
Section: Essential Oil Constituentssupporting
confidence: 86%
See 2 more Smart Citations
“…The main constituent was isopinocamphone that accounted for 34.00%, followed by pinocamphone (21.27%), β-Pinene (13.19 %), β-Phellandrene (13.10), α-Thujene (3.89 %) and Bicyclo-germacrene (3.47%). These results are well-matched with those of Jop et al, (2021), Aćimović et al, (2021, Hristova et al, (2015), Said-Al Ahl et al, (2015) and Stappen et al, (2015). They showed that isopinocamphone was the main component and followed by pinocamphone, β-pinene (8.8%), D-germacrene, bicyclo-germacrene, (E)-βcaryophyllene and α-elemol.…”
Section: Essential Oil Constituentssupporting
confidence: 86%
“…The authors found the main component of white hyssop was pinocamphone (51%) but pink hyssop contained equal amounts of pinocamphone (28.8%) and isopinocamphone (21.9%). The main constituents of H. officinalis essential oil were identified as pinocamphone, iso-pinocamphone, pinene, pinocarvone (Kizil et al, 2010, Fatemeh and Hamedeyazdan, 2011, Zheljazkov et al, 2012, Pandey et al, 2014, Said-Al Ahl et al, 2015and Hristova et al, 2015, Saeidi et al, 2020, Aćimović et al, 2021, Saebi et al, 2021and Jop et al, 2021. Venditti et al, (2015) detected linalool (35.3-51.2%) and methyl eugenol (7.3-22.7%) as the main compounds of H. officinalis essential.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, B. Jop et al (2021) proved that hyssop oil is saturated with monoterpene ketones, such as isopinocamphon -42.1% and pinocamphon -10.6%. Hyssop oil inhibits the germination of wheat and mustard, depending on the concentration.…”
Section: Figure 2 Index Of Allelopathic Activity Of Aerial Organs Of ...mentioning
confidence: 98%
“…antifungal activity against Candida albicans has been revealed for the soapwort root extract. the antimicrobial properties of soapwort root are associated with the presence of saponins, while those of hyssop herb are linked to the presence of essential oils (main constituents of isopinocamphone (40-50%) pinocamphone (10%), β-pinene, terpinen-4-ol, pinocarvone, carvacrol, p-cymene and myrtenal) [41,42]. the strong antimicrobial activity of this essential oil has been shown against Staphylococcus pyogenes, Staphylococcus aureus, Candida albicans and Escherichia coli, but not against Pseudomonas aeruginosa [43].…”
Section: Thyme Herb (Thymi Herba)mentioning
confidence: 99%